2018
DOI: 10.1016/j.envint.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal organochlorine pesticide exposure and the disruption of steroids and reproductive hormones in cord blood: The Hokkaido study

Abstract: Certain organochlorine pesticides (OCPs) are designated as persistent organic pollutants and are regulated in many countries. The effects of OCPs on pediatric endocrinology are a concern; however, only limited data exist from human studies on maternal OCP exposure and its effects on infants' hormone levels. This study was conducted as part of the Hokkaido Study Sapporo Cohort, a prospective birth cohort study in Japan. Participants included 514 women who enrolled at 23-35weeks of gestation between 2002 and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Sex hormone-binding globulin and prolactin (PRL) showed an inverse association with the OCPs. Among females, the linear regression model showed that only p,p′-dichlorodiphenyltrichloroethane was negatively associated with the level of DHEA and the adrenal androgen/glucocorticoid ratio, but was positively associated with cortisone levels [ 48 ]. Maternal PFOS levels had a significantly positive association with estradiol (E2), but a negative association with T/E2, progesterone (P4), and inhibin B.…”
Section: Resultsmentioning
confidence: 99%
“…Sex hormone-binding globulin and prolactin (PRL) showed an inverse association with the OCPs. Among females, the linear regression model showed that only p,p′-dichlorodiphenyltrichloroethane was negatively associated with the level of DHEA and the adrenal androgen/glucocorticoid ratio, but was positively associated with cortisone levels [ 48 ]. Maternal PFOS levels had a significantly positive association with estradiol (E2), but a negative association with T/E2, progesterone (P4), and inhibin B.…”
Section: Resultsmentioning
confidence: 99%
“…32) Moreover, prenatal DEHP exposure is reported to induce some adverse effects such as the disruption of adrenal androgens, glucocorticoids levels, IgE levels, and adipokine levels in cord blood, low birth weight and allergies and infectious diseases up to seven years of age. [33][34][35] Ait Bamai et al reported the median concentration of DiNP in floor dust taken from 128 houses in Japan was 140 μg/g, with a maximum concentration of 2,100 μg/g. 36) In addition, we reported the median concentration of DiNP in house dust taken from houses in Japan was 140 μg/g, with a maximum of 2,300 μg/g.…”
Section: Discussionmentioning
confidence: 99%
“…Ethiopia was also a signatory of this convention. Organochlorine pesticides generally increase the production of free radicals in the human body, and on the other hand decrease the activity of anti-oxidant enzymes, which leads to oxidative stress (Kumar et al 2010;Araki et al 2018). A recent case control study demonstrated the alterations in oxidative capacity among members of farmworkers exposed to a mixture of OCPs in Iran (Abbasi-Jorjandi et al 2020).…”
Section: Introductionmentioning
confidence: 99%